Analysis of Abdominal Massage Practice Performed by Traditional Birth Attendants in Mamba Community Health Center, East Nusa Tenggara - Banul, Maria Sriana; Halu, Silfia Angela N. (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: